Microencapsulation, Physicochemical Characterization, and Antioxidant, Antibacterial, and Antiplasmodial Activities of Holothuria atra Microcapsule - Prawesty Diah Utami; Herin Setianingsih; Dewi Ratih Tirto Sari (Scientifica)
This study provides the design of a microencapsulation formula, physicochemical characterization, and antioxidant, antibacterial, and antiplasmodial activities of Holothuria atra microcapsules. The ethanolic extract of H. atra was microencapsulated with chitosan (CHI) and sodium tripolyphosphate (Na-TPP) with various stirring times: 60 minutes (CHI60), 90 minutes (CHI90), and 120 minutes (CHI120). The microcapsules were then observed for physicochemical properties using scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The microcapsules were tested for antioxidant activity and antibacterial activity against Staphylococcus aureus and Escherichia coli using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Antiplasmodial bioactivity was assessed through in silico molecular docking. The CHI60 and CHI120 microcapsules exhibited a smaller size and an irregular spherical shape, while the same FTIR profile was observed in CHI90 and CHI120. The bioactivity tests demonstrated that CHI90 exhibited high antibacterial activity against E. coli and S. aureus, while CHI120 exhibited high antioxidant performance. Calcigeroside B and Echinoside B exhibited antiplasmodial activity against the Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH) protein, along with an artemisinin inhibition mechanism. In conclusion, the microcapsules with the CHI90 formula demonstrated the best antibacterial activity, while the CHI120 formula exhibited high antioxidant activity. Two terpenoids, Calcigeroside B and Echinoside B, exhibited the best antiplasmodial activity.